ARTEMIS: A Novel Mass-Spec Platform for HLA-Restricted Self and Disease-Associated Peptide Discovery - Finton, Kathryn A. K.; Brusniak, Mi-Youn; Jones, Lisa A.; Lin, Chenwei; Fioré-Gartland, Andrew J.; Brock, Chance; Gafken, Philip R.; Strong, Roland K. (Frontiers in Immunology, 2021)
Conventional immunoprecipitation/mass spectroscopy identification of HLA-restricted peptides remains the purview of specializing laboratories, due to the complexity of the methodology, and requires computational post-analysis to assign peptides to individual alleles when using pan-HLA antibodies. We have addressed these limitations with ARTEMIS: a simple, robust, and flexible platform for peptide discovery across ligandomes, optionally including specific proteins-of-interest, that combines novel, secreted HLA-I discovery reagents spanning multiple alleles, optimized lentiviral transduction, and streamlined affinity-tag purification to improve upon conventional methods. This platform fills a middle ground between existing techniques: sensitive and adaptable, but easy and affordable enough to be widely employed by general laboratories. We used ARTEMIS to catalog allele-specific ligandomes from HEK293 cells for seven classical HLA alleles and compared results across replicates, against computational predictions, and against high-quality conventional datasets. We also applied ARTEMIS to identify potentially useful, novel HLA-restricted peptide targets from oncovirus oncoproteins and tumor associated-antigens.